Impact of endoscopic thoracic R4 sympathicotomy combined with R3 ramicotomy for primary palmar hyperhidrosis - Huang, Yunhe; Liu, Yunkun; Zou, Wei; Mao, Na; Tang, Jian; Jiang, Lei; Zou, Guowen; Yang, Lun; Yu, Bentong; Wei, Guangxia (Frontiers in Surgery, 2023)
Background: Endoscopic thoracoscopic sympathectomy (ETS) is the preferred method for treating primary palmar hyperhidrosis (PPH) that bears the risk of compensatory hyperhidrosis (CH) following surgery. The current study aims to evaluate the effectiveness and safety of an innovative surgical procedure of ETS. Methods: A survey of the clinical data of 109 patients with PPH who underwent ETS in our department from May 2018 to August 2021 was retrospectively conducted. The patients were organized into two groups. Group A underwent R4 sympathicotomy combined with R3 ramicotomy. Group B underwent R3 sympathicotomy. Patients were followed up to evaluate the safety, effectiveness and the incidence of postoperative CH of the modified surgical approach. Results: A total of 102 patients completed follow-up, and seven of the total enrolled patients were lost to follow-up, with a loss rate of 6% (7/109). Among these, Group A constitutes 54 cases, group B constitutes 48 cases, and the mean follow-up was 14 months (interquartile range 12-23 months). There was no statistically difference in surgical safety, postoperative efficacy, and postoperative quality of life (QoL) score between group A and group B (p>0.05). The score of the psychological assessment was higher (p = 0.004) in group A (14.15±2.06) compared to group B (13.30±1.86). The incidence of CH in group A was lower than in group B (p = 0.019). Conclusion: R4 sympathicotomy combined with R3 ramicotomy is safe and effective for PPH treatment, along with a reduced incidence of postoperative CH rate and improved postoperative psychological satisfaction.